Preparation of GdCoO3 by Sol-Gel Method and Its Photocatalytic Activity. Issue 1 (2nd September 2021) - Zhang, Liqin; Chen, Haifeng; Xu, Yaohua; Tang, Peisong; Tong, Yanhua; Ding, Yangbin
Abstract: Using gadolinium nitrate, cobalt acetate, citric acid as main raw materials, GdCoO3 was successfully prepared by sol-gel method. The prepared samples were characterized by thermogravimetric differential scanning analysis (TG-DSC), X-ray diffraction analysis (XRD), scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy(FT-IR). Using methyl orange solution as simulated sewage, it was investigated that the effects of synthesis temperature and illumination time on photocatalytic activity of GdCoO3 . The results show that the pure cubic perovskite GdCoO3 samples can be prepared at calcination temperature of 700 °C to 1000 °C. The GdCoO3 calcined at 900 °C has uniform particles and an average grain size of about 0.5 μm to 1 μm. The photocatalytic performance of GdCoO3 calcined at 900 °C sample was the best. Under the condition of UV-light for 120 min, the photocatalytic degradation rate of methyl orange reached more than 96% in presence GdCoO3 calcined at 900 °C. This indicates that GdCoO3 has good photocatalytic performance.